Teachers' Readiness and Perceptions of Augmented Reality for Sustainable STEM Education - Sukmawati, Wati; Maarif, Samsul; Burhendi, Feli Cianda Adrin; Kadir, Kadzrina Abdul; Jamaludin, Norzalila Binti; Shaari, Hasnizam; Adlawan, Hendely A. (Balai Publikasi Indonesia, 2026)
This study explores teachers' readiness and perceptions regarding the integration of Augmented Reality (AR) in STEM education. The research, conducted with 250 teachers from Indonesia and Malaysia, uses an explanatory survey design and Structural Equation Modeling (SEM) to analyze a framework combining Teacher Readiness, the Technology Acceptance Model (TAM), and Deep Learning Orientation. The results reveal that Teacher Readiness significantly influences Perceived Ease of Use (β = 0.48) and Perceived Usefulness (β = 0.42), which in turn affect Attitude Toward Use (β = 0.31) and Behavioral Intention (β = 0.52). Behavioral intention strongly predicts Deep Learning Orientation (β = 0.57). The model explains 56% of the variance in Behavioral Intention and 32% in Deep Learning Orientation. Multi-group analysis shows that these findings are consistent across countries, genders, education levels, and age groups, demonstrating the robustness and generalizability of the model. This research highlights the importance of teacher readiness in adopting AR technology, which fosters deeper learning in STEM education